Toxicity of layered semiconductor chalcogenides: beware of interferences. Issue 83 (9th September 2015) - Latiff, Naziah; Teo, Wei Zhe; Sofer, Zdenek; Huber, Štěpán; Fisher, Adrian C.; Pumera, Martin
<x xml:space="preserve">Abstract</x> Layered semiconductor chalcogenides GaSe and GeS are new 2D materials with promising properties for solar energy conversion, field effect transistors and more. However, little is known about their toxicity effects, and we address this issue herein.